Inhibitory Receptors and Checkpoints in Human NK Cells, Implications for the Immunotherapy of Cancer - Sivori, Simona; Della Chiesa, Mariella; Carlomagno, Simona; Quatrini, Linda; Munari, Enrico; Vacca, Paola; Tumino, Nicola; Mariotti, Francesca Romana; Mingari, Maria Cristina; Pende, Daniela; Moretta, Lorenzo (Frontiers in Immunology, 2020)
The highly destructive mechanisms by which the immune system faces microbial infections is under the control of a series of inhibitory receptors. While most of these receptors prevent unwanted/excessive responses of individual effector cells, others play a more general role in immunity, acting as true inhibitory checkpoints controlling both innate and adaptive immunity. Regarding human NK cells, their function is finely regulated by HLA-class I-specific inhibitory receptors which allow discrimination between HLA-I+, healthy cells and tumor or virus-infected cells displaying loss or substantial alterations of HLA-I molecules, including allelic losses that are sensed by KIRs. A number of non-HLA-specific receptors have been identified which recognize cell surface or extracellular matrix ligands and may contribute to the physiologic control of immune responses and tolerance. Among these receptors, Siglec 7 (p75/AIRM-1), LAIR-1 and IRp60, recognize ligands including sialic acids, extracellular matrix/collagen or aminophospholipids, respectively. These ligands may be expressed at the surface of tumor cells, thus inhibiting NK cell function. Expression of the PD-1 checkpoint by NK cells requires particular cytokines (IL-15, IL-12, IL-18) together with cortisol, a combination that may occur in the microenvironment of different tumors. Blocking of single or combinations of inhibitory receptors unleashes NK cells and restore their anti-tumor activity, with obvious implications for tumor immunotherapy.